Stressed aquifers in the Lower Segura basin and the Vinalopó basin in Easter Spain - Andrés Sahuquillo (Ingeniería del Agua)
The carbonate aquifers of the Lower Segura Basin and the Vinalopó basin, along with some other granular aquifers are being exploited well above its average recharge for almost half a century. That causes a continuous decline of groundwater levels in most of the region, up to 5m/year in some cases and more than 300m from their initial situation in some areas, thus increasing the cost of groundwater pumping. The drop in levels produced the drying of springs and wetlands and increased salinity in some areas caused by the presence of saline formations. Against these problems is the increase in wealth created by the availability of water since the beginning of the intense exploitation of aquifers. The Water Framework Directive requires that aquifers being by 2015 in good quantitative and qualitative conditions, which is not possible, and neither would be delaying this date several decades. Simple analyses indicate that even eliminating pumping; groundwater would take between 100 and 1000years to recover. Several methods have been used for determining groundwater recharge and mathematical models that reproduce aquifer’s behaviour and could be used as valid tools for its management. The role that aquifers can play in the water resource management is discussed.